Mixed Governance Principles in the Gulf Lowlands of Mesoamerica - Stark, Barbara L.; Stoner, Wesley D. (Frontiers in Political Science, 2022)
With antecedents reaching back to the Olmec era (1500–600 BCE), complex societies from CE 300–900/1000 in the Gulf lowlands display architectural and material culture indications of both authoritarian and collective governance principles over two large areas, each with a distinctive version of a common architectural layout. The two areas include multiple polities adhering to particular layouts of structures providing key urban services. Our information derives from pedestrian surveys and mapping covering about 5,000 km2, plus remote sensing over 53,000 km2. Remote sensing reveals the extraordinary extent and consistency of the predominant architectural patterns. Starting with the Olmec era and continuing to CE 600 some sculpture glorifies individual rulers, but, at the same time, architecture shows the importance of corporate groups and public access to services that represent a more collective emphasis. Between CE 300 to 900, monumental platforms that supported palatial residences indicate powerful elites and rulers. Long mounds located on each side of the main plazas likely supported multiple rooms used by corporate civic groups. In some centers, multiple plaza groups attest to division of authority across several factions, as do chains of plazas in other cases. Thus, both authoritarian and collective principles are built into the design of urban centers. The replication of common architectural patterns across the study area suggests open networks of interaction consonant with low-density urbanism in the tropics. We concentrate our discussion of governance in south-central Veracruz during CE 300–900, for which we have more complete data, and we more briefly characterize the larger temporal and spatial framework. Eventually these urban networks collapsed due to a complex set of factors, but one ingredient may have been increasing disparities in wealth and corrosion of collective action.